Website Development and Digital Skill: The State of Traditional Media in European Minority Languages - Zabaleta, Iñaki; Gutierrez, Arantza; Ferre-Pavia, Carme; Fernandez, Itxaso; Urrutia, Santi; Xamardo, Nikolas (USC Annenberg School for Communication & Journalism, 2013)
This article examines the development of Internet websites by traditional news organizations operating in European minority languages. It also concerns journalists in those news outlets, specifically their perceptions of their own digital skill regarding online and multimedia journalism. Media and journalists of 10 European minority languages (Basque, Catalan, Galician, Corsican, Breton, Frisian, Irish, Welsh, Scottish-Gaelic, and Sámi) were studied using field methods, interviews, and a fairly representative survey of journalists in press, radio, and TV.